Cbl-b Deficiency Mediates Resistance to Programmed Death-Ligand 1/Programmed Death-1 Regulation - Fujiwara, Mai; Anstadt, Emily J.; Clark, Robert B. (Frontiers in Immunology, 2017)
Cbl-b is an E3 ubiquitin ligase that negatively regulates T cell activation. Cbl-b-/- T cells are hyper-reactive and co-stimulation independent, and Cbl-b-/- mice demonstrate robust T cell and NK cell-mediated anti-tumor immunity. As a result of these murine studies, Cbl-b is considered a potential target for therapeutic manipulation in human cancer immunotherapy. The PD-L1/PD-1 pathway of immune regulation is presently an important therapeutic focus in tumor immunotherapy and although Cbl-b-/- mice have been shown to be resistant to several immuno-regulatory mechanisms, the sensitivity of Cbl-b-/- mice to PD-L1-mediated suppression has not been reported. We now document that Cbl-b-/- T cells and NK cells are resistant to PD-L1/PD-1-mediated suppression. Using a PD-L1 Ig fusion protein, this resistance is shown for both in vitro proliferative responses and IFN-γ production and is not associated with decreased PD-1 expression on Cbl-b-/- cells. In co-culture studies, Cbl-b-/- CD8+, but not CD4+ T cells diminish the PD-L1 Ig-mediated suppression of bystander naïve WT CD8+ T cells. Using an in vivo model of B16 melanoma in which numerous liver metastases develop in WT mice in a PD-1 dependent manner, Cbl-b-/- mice develop significantly fewer liver metastases without the administration of anti-PD-1 antibody. Overall, our findings identify a new mode of immuno-regulatory resistance associated with Cbl-b deficiency and suggest that resistance to PD-L1/PD-1-mediated suppression is a novel mechanism by which Cbl-b deficiency leads to enhanced anti-tumor immunity. Our results suggest that targeting Cbl-b in cancer immunotherapy offers the opportunity to simultaneously override numerous relevant “checkpoints” including sensitivity to regulatory T cells, suppression by TGF-β, and immune-regulation by both CTLA-4, and as we now report, by the PD-L1/PD-1 pathway.